Gaseificação catalítica a vapor de pellets de capim elefante - Neuwald, Oscar de Almeida (My University, 2021)
There is a worldwide consensus on the need to replace fossil energy sources with renewable ones. Biomass is a promising alternative for replacing the use of fossil fuels. In addition, biomass contributes to the reduction of greenhouse gas emissions, since when subjected to a thermal process, it releases the carbon dioxide consumed by its photosynthesis. The main processes for obtaining energy from biomass are the thermochemical processes: pyrolysis, combustion, and gasification. Gasification has high energy efficiency, being a promising alternative for energy generation. The gasification process can be improved through the use of catalysts, in order to increase the yield in the production of syngas (Hydrogen and Carbon Monoxide). The alkali and alkaline earth metals can be present in the biomass, or be added to the gasification process, acting in the cracking of the tar for greater efficiency in the gasification reaction. Potassium (K) is an alkali metal present in biomass, which has a catalytic role in the gasification process, especially when steam is used as the gasification agent. Its concentration in biomass can be modified according to the fertilization during the planting of the biomass. Another catalyst for the gasification process is iron (Fe), nevertheless this metal is present in low concentrations in the biomass itself, and must be incorporated into it before its gasification. The use of iron as a catalyst becomes interesting due to its low toxicity and cost, having the ability to crack tar molecules, thus increasing the yield of gasification. In this sense, the scientific contribution of this work was to evaluate the effect of potassium and iron as catalysts in the process of gasification with steam of elephant grass pellets. Potassium and iron increased the conversion of elephant grass to steam gasification, in addition to an increase in the gas yield of the process. [resumo fornecido pelo autor]
É consenso mundial a necessidade da substituição de fontes fósseis de energia por fontes renováveis. As biomassas são uma alternativa promissora para a substituição da utilização de combustíveis fósseis. Além disto, a biomassa contribui para a redução das emissões dos gases causadores do efeito estufa (greenhouse gas), pois quando submetida a um processo térmico, libera o dióxido de carbono consumido pela sua fotossíntese. Os principais processos de obtenção de energia através de biomassa são os processos termoquímicos: pirólise, combustão e gaseificação. A gaseificação possui alta eficiência energética, sendo uma alternativa promissora de geração de energia. O processo de gaseificação pode ser aprimorado através da utilização de catalisadores, com o intuito de aumentar o rendimento na produção do gás de síntese (Hidrogênio e Monóxido de Carbono). Os metais alcalinos e alcalinos terrosos podem estar presentes na biomassa, ou serem adicionados ao processo de gaseificação, atuando no craqueamento do alcatrão para aumentar eficiência na reação de gaseificação. O potássio (K) é um metal alcalino presente nas biomassas, que possui papel catalítico no processo de gaseificação, em especial quando se utiliza vapor d?água como agente de gaseificação. A sua concentração na biomassa pode ser modificada conforme a adubação no plantio. Outro catalisador para o processo de gaseificação é o ferro (Fe), porém este metal está presente em baixas concentrações na biomassa, e deve ser incorporado a mesma antes de sua gaseificação. A utilização do ferro como catalisador torna-se interessante devido a sua baixa toxicidade e custo, tendo capacidade de craquear moléculas do alcatrão, elevando assim o rendimento da gaseificação. Neste sentido, a contribuição cientifica deste trabalho foi avaliar o efeito do potássio e do ferro como catalisadores do processo de gaseificação com vapor d?água de pellets de capim elefante. O potássio e o ferro elevaram a conversão do capim elefante na gaseificação a vapor, além de um aumento no rendimento de gás do processo. [resumo fornecido pelo autor]
Keywords: Biocombustíveis; Biomassa; Capim-elefante; Catalisadores; Biofuels; Biomass; Elephant grass; Catalysts